2019
DOI: 10.1002/smll.201900501
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targeting‐Mediated Mild‐Temperature Photothermal Therapy with a Smart Albumin‐Based Nanodrug

Abstract: Photothermal therapy (PTT) usually requires hyperthermia >50 °C for effective tumor ablation, which inevitably induces heating damage to the surrounding normal tissues/organs. Moreover, low tumor retention and high liver accumulation are the two main obstacles that significantly limit the efficacy and safety of many nanomedicines. To solve these problems, a smart albumin‐based tumor microenvironment‐responsive nanoagent is designed via the self‐assembly of human serum albumin (HSA), dc‐IR825 (a cyanine dye and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 191 publications
(96 citation statements)
references
References 88 publications
0
96
0
Order By: Relevance
“…Phototherapy, including photothermal therapy (PTT) and photodynamic therapy (PDT), are widely used to treat infections and exhibit a distinct advantage over conventional chemical antimicrobial agents 27 . Considering the complex structure of the eye, a bactericidal strategy of mild temperature photothermal assisted therapy, which remains the antibacterial effect but reduces thermal damage to nearby tissues, is more suitable for endophthalmitis 28 , 29 . PDT, which can produce reactive oxygen species (ROS), also shows antibacterial ability while it can improve the treatment effects and decrease side effects of PTT 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Phototherapy, including photothermal therapy (PTT) and photodynamic therapy (PDT), are widely used to treat infections and exhibit a distinct advantage over conventional chemical antimicrobial agents 27 . Considering the complex structure of the eye, a bactericidal strategy of mild temperature photothermal assisted therapy, which remains the antibacterial effect but reduces thermal damage to nearby tissues, is more suitable for endophthalmitis 28 , 29 . PDT, which can produce reactive oxygen species (ROS), also shows antibacterial ability while it can improve the treatment effects and decrease side effects of PTT 30 .…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of BSA, the product was agglomerated with large size ( Figure S1, Supporting Information), indicating that BSA plays a key role in promoting 1D nanorods formation. [43][44][45] Typically, atomic force microscopy (AFM) (Figure 1b,c) and transmission electron microscopy (TEM) images (Figure 1d,e) showed that the size of Te-Gd was similar to that of Te without Gd adding ( Figure S2, Supporting Information). The lattice fringes of Te-Gd were measured to be 0.389 and 0.323 nm, respectively (Figure 1f), which were in consistent with the (1 0 0) and (1 0 1) crystal planes of hexagonal Te (JCPDS # 04-0554), respectively, and match well with the result of Figure 1g.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, we investigated the cell endocytic pathways of HA-IR825-Chol by using 4T1 cells. Chlorpromazine (CPZ) hydrochloride, genistein, 5-(N,Ndimethyl)-amiloride (amiloride), methyl-β-cyclodextrin (MβCD), and 4°C treatment were used to inhibit clathrinmediated, caveolae-mediated, macropinocytosis-dependent, lipid raft-mediated, and energy-dependent pathway, respectively [69]. The flow cytometric results in Fig.…”
Section: Cellular Uptake Behavior and Cytotoxicity Of Ha-ir825-chol Npsmentioning
confidence: 99%